Optimizing the digital economy to improve financial inclusion in Indonesia - samosir, Suryany (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study aims to analyze the role of the digital economy in improving financial inclusion in Indonesia, as well as the challenges and opportunities associated with its implementation. Along with the rapid development of information and communication technology, the digital economy sector, particularly digital financial services or fintech, has opened access to finance for previously marginalized communities, such as those living in remote areas, MSMEs, and low-income groups. This study uses a systematic literature review approach to explore the various factors influencing the expansion of the digital economy in Indonesia, including government policies, existing regulations, and their impact on improving financial literacy. The findings show that while the digital economy has great potential to improve financial inclusion, there are significant barriers, such as inequality in internet access between urban and rural areas, regulatory challenges, and issues related to cybersecurity and personal data protection. To optimize the benefits of the digital economy, a collaborative role between the government, private sector and society is needed to overcome these barriers and develop policies that support inclusive and safe growth of the digital economy. This research provides recommendations to improve digital infrastructure, strengthen digital literacy, and create adaptive regulations to ensure that all levels of society can equally benefit from the digital economy